Mixed matrix membrane for ammonia separation and preparation method thereof
By blending mixed matrix membranes with ether-rich block polymer Pebax and liquid adsorbent, the existing ammonia separation membranes have solved the problems of low ammonia selectivity and penetration flux, and achieved high-efficiency and low-energy-consuming ammonia separation effect.
Patent Information
- Application Number
- CN202411177852.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The existing ammonia separation membrane has low ammonia selectivity and low ammonia permeability flux, making it difficult to achieve efficient and low energy consumption ammonia separation.
The mixed matrix membrane is prepared by blending the block polymer Pebax rich in ether bonds and a liquid adsorbent with high ammonia selective adsorption and high ammonia adsorption capacity. The high selectivity and high throughput permeability of ammonia are achieved through membrane separation technology.
Continuous, fast and low-energy separation of ammonia is achieved, with ammonia permeability up to 2656.9 Barrer, and ammonia/nitrogen and ammonia/hydrogen selectivity up to 594.1 and 150.8, respectively.
Smart Images

Figure HDA0005165312670000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new chemical materials, and in particular to a mixed matrix membrane for ammonia separation and a preparation method thereof. Background Art
[0002] Ammonia plays an important role in the chemical industry and has important applications in the fields of agricultural fertilizers, pharmaceuticals, organic compounds and polymer material synthesis. So far, most ammonia is still produced through the traditional Haber-Bosch process, which produces ammonia through the catalytic reaction of nitrogen and hydrogen under high temperature and high pressure conditions. It must be noted that the ammonia synthesis conversion rate of the Haber-Bosch process is low, only 10-20%, and is generally collected by physical cooling and liquefaction. However, about 3% of ammonia will still remain in the circulating gas, reducing the synthesis efficiency and affecting production capacity. Therefore, it is very important to recover low-concentration ammonia.
[0003] Common ammonia separation methods include physical condensation, liquid absorption, solid adsorption and membrane separation. The physical condensation method requires cooling ammonia to its condensation point (usually around -33°C), which consumes a lot of energy and is costly. Liquid absorption uses the higher solubility of ammonia hydrogen in liquid solvents relative to hydrogen and nitrogen to achieve ammonia separation. The earliest used liquid adsorbents were water and inorganic acid adsorbents. However, they have the disadvantages of high volatility and hot melting, high corrosiveness and irreversible absorption. Ionic liquids and low eutectic solvents are emerging ammonia liquid absorbents. The ammonia absorption and separation process based on the two can reduce energy consumption, operating costs and net carbon dioxide emissions to a certain extent. However, the viscosity of ionic liquids and low eutectic solvents is relatively large, which makes it difficult to transport the two in reaction towers and pipelines. Compared with liquid absorption, solid adsorption does not have volatility, viscosity or corrosiveness problems. However, there is a significant common problem between solid adsorption and liquid adsorption, that is, desorption must be performed after adsorption to obtain ammonia products. The phase change of ammonia in this process leads to increased energy consumption, and ammonia cannot be polymerized after the adsorbent reaches saturation, that is, continuous ammonia separation cannot be achieved.
[0004] In recent years, membrane separation technology has also been gradually applied in the ammonia separation process of synthetic ammonia. Compared with absorption and adsorption methods, membrane separation does not involve component phase change and has lower energy consumption. At the same time, membrane separation also has the characteristics of continuous production, simple process, green and pollution-free. Existing ammonia separation membranes have low ammonia selectivity and low ammonia permeation flux. So far, ammonia separation membranes with both high performance and low cost are still a severe technical challenge. Summary of the invention
[0005] In view of the problems of low ammonia selectivity and low ammonia permeation flux of ammonia separation membranes in the prior art, the present invention provides a mixed matrix membrane for ammonia separation and a preparation method thereof, wherein a block polymer rich in ether bonds and a liquid adsorbent having both high ammonia selective adsorption and high ammonia adsorption capacity are blended to prepare a mixed matrix membrane, thereby providing a mixed matrix ammonia separation membrane having both high ammonia selective permeability and high ammonia permeation flux.
[0006] The present invention adopts the following technical solution:
[0007] A method for preparing a mixed matrix membrane for ammonia separation comprises the following steps:
[0008] S1, dissolving polyether block polyamide (Pebax) and a liquid adsorbent in a solvent, and refluxing and stirring to obtain a film casting solution;
[0009] S2. After the casting solution is cooled to room temperature, a film is coated on the substrate, and then heated for 1-24 hours to obtain a mixed matrix membrane.
[0010] In the step S1, the liquid adsorbent is selected from one of ethylamine hydrochloride + phenol low eutectic agent (molar ratio 1: 1-8), ethylamine hydrochloride + resorcinol low eutectic agent (molar ratio 1: 0.5-2), ethylamine hydrochloride + phloroglucinol low eutectic agent (molar ratio 1: 0.5-2), imidazole hydrochloride + glycerol low eutectic agent (molar ratio 1: 1-4), ethylamine hydrochloride + cobalt chloride + glycerol low eutectic solvent (molar ratio 1: (0.2-1): 3), ethanolamine hydrochloride + glycerol low eutectic solvent (molar ratio 1: 2-6), ethanolamine hydrochloride + phenol low eutectic solvent (molar ratio 1: 2-6), glycolic acid + phenol low eutectic solvent (molar ratio 1: 1-5), lithium-triethylene glycol chelated ionic liquid, and diethanolamine hydrochloride ionic liquid. The structural formula of each liquid adsorbent is as follows Figure 1 As shown;
[0011] In the step S1, the mass ratio of the polyether block polyamide to the liquid adsorbent is 1:4 to 4:1.
[0012] The solvent in step S1 is an organic solvent that can dissolve the polyether block polyamide and the liquid adsorbent at the same time.
[0013] Preferably, the solvent is one or more combinations of N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide and ethanol.
[0014] The reflux stirring time in step S1 is 1-24h.
[0015] The mass concentration of the casting solution in step S1 is 1%-20%.
[0016] The heating temperature of the coating film in step S2 is 40-120°C.
[0017] A mixed matrix membrane for ammonia separation prepared according to the preparation method.
[0018] The technical solution of the present invention has the following advantages:
[0019] A. The present invention uses Pebax and a liquid adsorbent to blend and prepare a mixed matrix membrane. Pebax is a block polymer Pebax composed of two chain segments, polyethylene oxide (PEO) and polyamide (PA). The former can promote the selective permeation of ammonia by interacting with ammonia, and the latter provides strong film-forming mechanical properties. The selected multiple liquid adsorbents have high ammonia selective adsorption and high ammonia adsorption capacity. Through the synergistic effect of Pebax and the liquid adsorbent, the high selectivity and high-flux permeation of ammonia are simultaneously promoted. According to the preparation method of the present invention, a mixed matrix membrane is prepared and ammonia separation is performed by membrane separation, which can achieve continuous, rapid, and low-energy separation of ammonia.
[0020] B. The mixed matrix membrane obtained by the present invention has a highly efficient ammonia separation effect. When separating the residual gas of synthetic ammonia, the ammonia permeability is as high as 2656.9 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities are as high as 594.1 and 150.8, respectively.
[0021] C. The raw materials for preparing the mixed matrix membrane of the present invention are either commercially available or can be synthesized at low cost, thereby greatly reducing the cost of membrane preparation and facilitating its large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The structural formulas of the liquid adsorbents are described below. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Embodiment 1:
[0025] Add 1g Pebax, 0.25g ethylamine hydrochloride + phenol low eutectic agent (the mass ratio of Pebax and liquid adsorbent is 4:1) and 11.25g dimethyl sulfoxide into a single-necked flask, reflux and stir for 8 hours to obtain a casting solution with a mass concentration of 10%, coat the solution on a glass plate after cooling, and heat at 120°C for 12 hours to obtain a mixed matrix membrane.
[0026] A gas separation device was used to separate a mixed gas containing ammonia, nitrogen and hydrogen, and the permeabilities of the three gases were tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the pure ammonia permeability of the mixed matrix membrane was 658.3 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 480.5 and 85.7, respectively.
[0027] Embodiment 2:
[0028] Add 1g Pebax, 1g ethylamine hydrochloride + phenol low eutectic agent (the mass ratio of Pebax and liquid adsorbent is 1:1) and 18g dimethyl sulfoxide into a single-necked flask, reflux and stir for 8 hours to obtain a casting solution with a mass concentration of 10%, coat the solution on a glass plate after cooling, and heat at 120°C for 24 hours to obtain a mixed matrix membrane.
[0029] A gas separation device was used to separate a mixed gas containing ammonia, nitrogen and hydrogen, and the permeabilities of the three gases were tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the pure ammonia permeability of the mixed matrix membrane was 813.7 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 529.5 and 114.3, respectively.
[0030] Embodiment 3:
[0031] Add 1g Pebax, 4g ethylamine hydrochloride + phenol eutectic agent (the mass ratio of Pebax to liquid adsorbent is 1:4) and 45g dimethyl sulfoxide into a single-necked flask, reflux and stir for 8 hours to obtain a casting solution with a mass concentration of 10%, coat the solution on a glass plate after cooling, and heat at 120°C for 24 hours to obtain a mixed matrix membrane.
[0032] A gas separation device was used to separate a mixed gas containing ammonia, nitrogen and hydrogen, and the permeabilities of the three gases were tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the ammonia permeability of the mixed matrix membrane was 2656.9 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 594.1 and 150.8, respectively.
[0033] Comparative Example 1:
[0034] 1 g of Pebax and 9 g of dimethyl sulfoxide were added to a single-necked flask, and the mixture was refluxed and stirred for 8 h to obtain a casting solution with a mass concentration of 10%. After cooling, the solution was coated on a glass plate and heated at 120° C. for 24 h to obtain a Pebax membrane.
[0035] A gas separation device was used to separate a mixed gas containing ammonia, nitrogen and hydrogen, and the permeabilities of the three were tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the pure ammonia permeability of the Pebax membrane was 590.2 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 404.3 and 68.5, respectively, which were close to those reported in the literature. This is because the polyether unit of Pebax has a strong affinity with polar gases and has good polar gas separation performance. Ammonia is a highly polar alkaline gas, so the Pebax membrane has a certain ammonia separation performance.
[0036] Combining Examples 1-3 and Comparative Example 1, it can be seen that the addition of the liquid adsorbent significantly improves the ammonia separation performance of the mixed matrix membrane. At the same time, as the amount of liquid adsorbent added increases, the ammonia permeability and ammonia selectivity of the mixed matrix membrane are simultaneously improved.
[0037] Embodiment 4:
[0038] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the mass concentration of the casting solution was changed to 1%, and similar results were obtained.
[0039] Embodiment 5:
[0040] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the mass concentration of the casting solution was changed to 20%, and similar results were obtained.
[0041] Embodiment 6:
[0042] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the organic solvent was changed to ethanol, the heating temperature of the casting solution was changed to 40° C., and the heating time was changed to 1 h, and similar results were obtained.
[0043] Embodiment 7:
[0044] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the organic solvent was changed to N-methylpyrrolidone, and similar results were obtained.
[0045] Embodiment 8:
[0046] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the organic solvent was changed to NN dimethylformamide and the reflux stirring time was 24 h, and similar results were obtained.
[0047] Embodiment 9:
[0048] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the organic solvent was changed to NN-dimethylacetamide and the reflux stirring time was 1 h, and similar results were obtained.
[0049] Embodiment 10:
[0050] A mixed matrix membrane was prepared using a method similar to that of Example 3, except that the organic solvent was changed to methanol, and similar results were obtained.
[0051] Embodiment 11:
[0052] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the liquid adsorbent was changed to ethylamine hydrochloride + resorcinol eutectic agent, and similar results were obtained.
[0053] Embodiment 12:
[0054] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the liquid adsorbent was changed to ethylamine hydrochloride + phloroglucinol eutectic agent, and similar results were obtained.
[0055] Embodiment 13:
[0056] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the liquid adsorbent was changed to imidazole hydrochloride + glycerol eutectic agent, and similar results were obtained.
[0057] Embodiment 14:
[0058] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the liquid adsorbent was changed to a low eutectic solvent of ethylamine hydrochloride + cobalt chloride + propylene glycol, and similar results were obtained.
[0059] Embodiment 15:
[0060] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the liquid adsorbent was changed to ethanolamine hydrochloride + glycerol low eutectic solvent, and similar results were obtained.
[0061] Embodiment 16:
[0062] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the liquid adsorbent was changed to ethanolamine hydrochloride + phenol low eutectic solvent, and similar results were obtained.
[0063] Embodiment 17:
[0064] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the liquid adsorbent was changed to a glycolic acid + phenol low eutectic solvent, and similar results were obtained.
[0065] Embodiment 18:
[0066] A mixed matrix membrane was prepared by a method similar to that of Example 3, except that the liquid adsorbent was changed to a lithium-triethylene glycol chelated ionic liquid, and similar results were obtained.
[0067] Embodiment 19:
[0068] A mixed matrix membrane was prepared using a method similar to that of Example 3, except that the liquid adsorbent was changed to diethanolamine hydrochloride ionic liquid, and similar results were obtained.
[0069] In summary, the present invention uses Pebax and a liquid adsorbent to blend and prepare a mixed matrix membrane. Pebax is a block polymer Pebax composed of two segments, polyethylene oxide (PEO) and polyamide (PA). The former can promote the selective permeation of ammonia by interacting with ammonia, and the latter provides strong film-forming mechanical properties. The selected liquid adsorbents have high ammonia selective adsorption and high ammonia adsorption capacity. Through the synergistic effect of Pebax and the liquid adsorbent, the high selectivity and high-flux permeation of ammonia are simultaneously promoted. According to the preparation method of the present invention, a mixed matrix membrane is prepared and ammonia separation is performed by membrane separation, which can achieve continuous, rapid, and low-energy separation of ammonia.
[0070] The mixed matrix membrane obtained by the present invention has a highly efficient ammonia separation effect. When separating the residual gas of synthetic ammonia, the ammonia permeability can reach up to 2656.9 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities are as high as 594.1 and 150.8, respectively.
[0071] The raw materials for preparing the mixed matrix membrane of the present invention are either commercially available or can be synthesized at low cost, thereby greatly reducing the cost of membrane preparation and facilitating its large-scale application.
[0072] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A method for preparing a mixed matrix membrane for ammonia separation, characterized in that: The following steps are involved: S1, dissolving polyether block polyamide (Pebax) and a liquid adsorbent in a solvent, and refluxing and stirring to obtain a film casting solution; S2. After the casting solution is cooled to room temperature, a film is coated on the substrate, and then heated for 1-24 hours to obtain a mixed matrix membrane.
2. The preparation method according to claim 1, characterized in that: In the step S1, the liquid adsorbent is selected from one of ethylamine hydrochloride + phenol low eutectic agent, ethylamine hydrochloride + resorcinol low eutectic agent, ethylamine hydrochloride + phloroglucinol low eutectic agent, imidazole hydrochloride + glycerol low eutectic agent, ethylamine hydrochloride + cobalt chloride + glycerol low eutectic solvent, ethanolamine hydrochloride + glycerol low eutectic solvent, ethanolamine hydrochloride + phenol low eutectic solvent, glycolic acid + phenol low eutectic solvent, lithium-triethylene glycol chelated ionic liquid, and diethanolamine hydrochloride ionic liquid.
3. The preparation method according to claim 1, characterized in that: In the step S1, the mass ratio of the polyether block polyamide to the liquid adsorbent is 1:4 to 4:
1.
4. The preparation method according to claim 1, characterized in that: The solvent in step S1 is an organic solvent that can dissolve the polyether block polyamide and the liquid adsorbent at the same time.
5. The preparation method according to claim 4, characterized in that: The solvent is one or more combinations of N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide and ethanol.
6. The preparation method according to claim 1, characterized in that: The reflux stirring time in step S1 is 1-24h.
7. The preparation method according to claim 1, characterized in that: The mass concentration of the casting solution in step S1 is 1%-20%.
8. The preparation method according to claim 1, characterized in that: The heating temperature of the coating film in step S2 is 40-120°C.
9. A mixed matrix membrane for ammonia separation obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Plasma-processing multilayer gas composite membrane, preparation method and application thereof
CN109701399A
Method for selectively separating ammonia gas by using multi-site proton type ionic liquid composite membrane
CN111467933A
Amino acid ionic liquid-coated nanosphere / polymer hybrid membranes for CO2 separation
CN111804161A
Method for separating ammonia and carbon through ionic liquid membrane
CN113893709A
Preparation method and application of mixed matrix membrane based on modified aluminum trioxide and Pebax
CN115282791A
Cited By
Ethanolamine modified KMnF3at-Zn-MOF-74 mixed matrix membrane and preparation method thereof
CN121819612A